The Association Between Depressive Symptoms and Insomnia in College Students in Qinghai Province: The Mediating Effect of Rumination - Xiao, Shuheng; Liu, Shuai; Zhang, Puxiao; Yu, Jia; A, Huaihong; Wu, Hui; Zhang, Fabin; Xiao, Yulan; Ma, Naiben; Zhang, Xiuqin; Ma, Xiaoxia; Li, Junfeng; et al. (Frontiers in Psychiatry, 2021)
Background: This study investigates the mediating effect of rumination on the associations between depressive symptoms and insomnia. Methods: This is a cross-sectional study. Insomnia Severity Index (ISI), Ruminant Response Scale (RRS) and Beck Depression Inventory (BDI) were determined in 12,178 college students in Qinghai province by a questionnaire network platform. Results: The prevalence of insomnia was 38.6% in the participants. Insomnia symptoms (interquartile range: 6 [3, 9]), depressive symptoms (interquartile range: 5 [1, 9]), and rumination (interquartile range: 22 [20, 26]) were positively correlated (r = 0.25 - 0.46, p < 0.05). Mediation effect analysis showed that the depressive symptoms affected insomnia directly and indirectly. The direct effect and the indirect effect through rumination account for 92.7% and 7.3% of the total effect, respectively. Conclusion: Rumination mediates the association between depressive symptoms and insomnia symptoms.